Acute respiratory distress syndrome caused by Mycoplasma pneumonia without elevated pulmonary vascular permeability: a case report - Takahashi, Naoki; Shinohara, Tsutomu; Oi, Rie; Ota, Muneyuki; Toriumi, Shinichi; Ogushi, Fumitaka (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Sporadic patients with acute respiratory distress syndrome (ARDS) caused by Mycoplasma pneumoniae have been reported. However, knowledge about the pathophysiology and pharmacological treatment of this condition is insufficient. Moreover, the pulmonary vascular permeability in ARDS related to M. pneumoniae infection has not been reported. We report a case of ARDS caused by Mycoplasma pneumoniae without elevated pulmonary vascular permeability, which was successfully treated using low-dose short-term hydrocortisone, suggesting that pulmonary infiltration in ARDS caused by Mycoplasma pneumoniae does not match the criteria of permeability edema observed in typical ARDS.